Research of Output Characteristic and Design of a Swing SMA Movable Tooth Drive Actuator - Yaqi Jiang; Lizhong Xu (Jixie chuandong)
A kind of swing movable teeth transmission drive actuator with SMA（Shape memory alloy） is designed， and the working principle of this kind of actuator is described. According to phase change mechanism of SMA wires and coupled mechanical model of movable teeth drive， the output torque of the drive is deduced. For the specific situation， the general design method of the actuator is given. The effects of the mutual coupling parameters such as the swinging rod amplification coefficient and the eccentricity of the movable tooth on the output characteristics of the drive are investigated， and the optimal range of the key parameters is given. The ideas and methods for the optimization and output characteristic analysis of the movable teeth drive actuator with SMA are provided.